2001
DOI: 10.1159/000047714
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Depression, Antidepressant Treatment and Rehabilitation Results

Abstract: The aim of this study was to assess the specific influence of poststroke depression (PSD) on both basal functional status and rehabilitation results. We performed a case-control study in 290 stroke inpatients, matched for age (±1 year) and onset admission interval (±3 days) and divided in two groups according to the presence (PSD+) or absence (PSD–) of PSD. All PSD+ patients were treated with antidepressants (AD), mainly with fluoxetine. PSD+ patients, despite similar severity of stroke, showed greater disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 43 publications
5
57
0
9
Order By: Relevance
“…Post-stroke depression has negative effects on functional recovery (Parikh et al, 1990;Kotila et al, 1999), and these effects can be overcome by pharmacological treatment of depression (Gainotti et al, 2001). Although antidepressants have been effectively used to treat post-stroke depression (Primeau, 1988;Gainotti et al, 2001;Paolucci et al, 2001), their prescription is critically influenced by their safety, tolerability, and their impact on co-morbid conditions (Rampello et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Post-stroke depression has negative effects on functional recovery (Parikh et al, 1990;Kotila et al, 1999), and these effects can be overcome by pharmacological treatment of depression (Gainotti et al, 2001). Although antidepressants have been effectively used to treat post-stroke depression (Primeau, 1988;Gainotti et al, 2001;Paolucci et al, 2001), their prescription is critically influenced by their safety, tolerability, and their impact on co-morbid conditions (Rampello et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A report described that there was no relationship between the existence of PSD and the restoration of function 30) . However, it was demonstrated that a group without PSD achieved good restoration of ADL, two times better than a group with PSD 5) , and that the restoration of ADL was advanced by recovery from PSD 31) . Another study reports that the degree of restoration of ADL showed a difference of 30 percent according to whether or not treatment of PSD had been carried out 32) .…”
Section: Discussionmentioning
confidence: 96%
“…So far, age 2,3) , gender 4) , and depression 5) have been reported as factors influencing Activities of Daily Living (ADL).…”
Section: Introductionmentioning
confidence: 99%
“…Постин-сультные депрессии встречаются значительно чаще других аффективных расстройств, чем объясняется повышенное внимание к этой проблеме уже многие годы [19,20]. Часто-та депрессии, по данным разных авторов [21][22][23][24], варьирует от 6 до 60%, составляя в среднем 20-30% .…”
Section: о б з о р ыunclassified